P18. Predictive role of serum tumor markers NSE and TK in patients with advanced-stage NSCLC treated with EGFR-TKIs - Fiala, Ondrej (Transl Lung Cancer Res, 2014)
BACKGROUND: Targeted treatment based on tyrozine kinase inhibitors (TKI) directed at epidermal growth factor receptor (EGFR) represents a novel effective tool in management of advanced-stage non-small cell lung cancer (NSCLC). Although, activating EGFR gene mutations represent currently the strongest predictor of EGFR-TKIs efficacy, the majority of NSCLC patients harbor wild-type EGFR gene and moreover there is still a large proportion of patients in whom it is not feasible to acquire an adequate tissue for EGFR mutation analysis. We focused on the predictive of pretreatment levels of neuron-specific enolase (NSE) and thymidin kinase (TK) in patients with advanced-stage NSCLC treated with EGFR-TKIs. METHODS: Pretreatment serum levels of NSE and TK were measured in 163 patients with advanced-stage (IIIB, IV) NSCLC treated with erlotinib or gefitinib. Serum levels of NSE were measured using immunoradiometric titration method (IRMA) and levels of TK were measured using radioenzymatic assay (REA). Comparison of patients’ survival [progression-free survival (PFS) and overall survival (OS)] according to the level of assessed tumor markers was performed using the log-rank test. RESULTS: For patients with high NSE the median PFS and OS was 1.1 and 3.7 compared to 2.6 and 11.6 months for patients with low NSE (P=0.002 and P=0.003). For patients with high TK the median PFS and OS was 2.1 and 8.5 compared to 2.9 and 17.4 months for patients with low TK (P=0.026 and P=0.020). The multivariate Cox proportional hazards model revealed that high level of NSE was significant independent predictive factor for short PFS (HR=2.36; 95% CI: 1.34-4.17; P=0.003). CONCLUSIONS: The study proved that high pretreatment levels of NSE predict low efficacy of EGFR-TKI treatment in patients with advanced-stage NSCLC. Assessment of NSE levels is a feasible predictive tool for EGFR-TKI treatment efficacy especially for patients with unknown EGFR mutation status.